RANCANG BANGUN SISTEM PENDETEKSI PENGGUNAAN SAFETY HELMET PADA ENGINE ROOM BERBASIS ARDUINO - Eka Putri, Anggraeini; Syahputra Simatupang, Rama; Sianturi, Intan; Retno Gunarti, Monika; Dai Robbi, Shofa (Penerbit Lafadz Jaya, 2026)
Maritime safety demands innovative solutions amid rising engine room accidents from non-compliance with personal protective equipment like safety helmets, contributing 15-20% of global incidents. This study aimed to design and build an Arduino Pro Micro-based helmet detection system using micro switches and buzzers for real-time alerts in harsh ship environments. Employing a Research and Development (R&D) approach with ADDIE model, the prototype was tested on 10 engine crew (ABK) aboard KMP JAMBO IX via purposive sampling. Instruments included Arduino IDE for programming, serial monitors for data logging, and SPSS 26 for t-test analysis (p<0.05). Results showed 100% micro switch accuracy, 15-second buzzer response, and 7-hour battery life across four tests, reducing SOP violations from observed pre-implementation lapses. In conclusion, the system enhances crew discipline and supervision efficiency, bridging gaps in affordable maritime IoT safety tools, with potential to cut head injuries by 20-30%.